2006
DOI: 10.1038/sj.bjc.6603004
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin alfa in platinum-treated ovarian cancer patients: results of a multinational, multicentre, randomised trial

Abstract: This multicentre, open-label, controlled clinical trial assessed the effects of epoetin alfa treatment on haematologic and quality of life (QOL) parameters in 182 anaemic (Hbp12 g dl À1 ) ovarian cancer patients receiving platinum chemotherapy. Patients were randomised 2 : 1 to receive epoetin alfa 10 000 -20 000 IU three times weekly plus best standard treatment (BST) or BST only. Main study end points were changes from baseline in haemoglobin (Hb) level, transfusion requirements, and QOL. For the epoetin alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…A randomised study on 182 patients with ovarian cancer under chemotherapy and erythropoietin alpha TTW or the best possible treatment reports benefits on QOL for the group under treatment, where these benefits are attributed to increments observed in the LASA scale (p ( ( =0.004) [32].…”
Section: Erythropoietin Alphamentioning
confidence: 99%
“…A randomised study on 182 patients with ovarian cancer under chemotherapy and erythropoietin alpha TTW or the best possible treatment reports benefits on QOL for the group under treatment, where these benefits are attributed to increments observed in the LASA scale (p ( ( =0.004) [32].…”
Section: Erythropoietin Alphamentioning
confidence: 99%
“…Additional studies incorporating costs and patient quality of life are needed. 21 †Extended Cox model with 2 heaviside functions. 18 ‡Cox proportional hazards model.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review it has been suggested that optimal clinical benefit from erythropoietic treatment of chemotherapy-induced anaemia may be achieved through early intervention [39]. Previous studies defined an epoetin alfa start at Hb < 12.1 g/dl as early intervention [30][31][32]. In case early intervention is used, it is to be recommended that Hb levels are closely monitored since two recent publications concerning erythropoietin treatment in cancer patients with mild anaemia described increased mortality in the erythropoietin treated patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, often response is defined as an Hb increase ≥2 g/dl independent of any blood transfusion in the 4 weeks before response was reached (response-1) [5,6,8,10,27]. In recent studies response was defined as an Hb increase ≥1 g/dl, independent of blood transfusions, after 4 weeks epoetin alfa treatment (response-2) [24,[28][29][30]. Both these response definitions were retrospectively applied to the epoetin alfa treated lung cancer patients in this observational study.…”
Section: Methodsmentioning
confidence: 99%